The validity and reliability of culturally responsive leadership practice instruments in small schools peninsular Malaysia - Mohd Norlizam Mohd Razali; Aida Hanim A. Hamid; Bity Salwana Alias; Azlin Norhaini Mansor (International Journal of Evaluation and Research in Education (IJERE), 2024)
A culturally responsive leadership instrument was developed to determine the level of culturally responsive leadership practice of headmasters in small schools in Peninsular Malaysia. This study was conducted in Perak and Negeri Sembilan to determine the instrument’s reliability and validity. Exploratory factor analysis (EFA) and item reliability analysis were used to determine the questionnaire’s reliability and validity. Next, the average congruence percentage (ACP) is used to determine the reliability test between expert assessors. Experts approved the validity and reliability of the instrument before the EFA test was conducted. All four constructs have high-reliability index values between 0.88–0.93. Next, the EFA analysis shows four dimensions in the culturally responsive leadership instrument with factor loadings ranging from 0.62–0.88. The findings also show that the variance explained in the data is 65.16% with an eigenvalue greater than 1. This result showed that all items are received with high approval. In addition, the reliability coefficient α=0.93 is very high. The results prove that this culturally responsive leadership instrument has high validity and reliability and can measure the level of culturally responsive leadership implementation practices in small schools in Peninsular Malaysia.